Swallows and Humans in Wales: historical and modern feeding strategies - Lee Raye (Medieval Animal Data-Network, 2017)
The barn swallow (Hirundo rustica ) is a highly successful species of bird found on every continent. It is commensal with humans and has a long history of exploiting human industry for its home and food. After a very brief species history, this article provides a modern case study, looking at the behaviour of swallows at Cardiff University in Wales to inform a new reading of the metaphor of the swallow and the sea-swallow in the medieval Welsh ‘Culhwch ac Olwen’.